Deposit insurance systems: Promoters of banking stability? - Sivarajah, Ganesh (2017)
During the recent global financial crisis, regulators and policymakers turned to deposit insurers, along with monetary and fiscal measures, to help restore market confidence and promote financial stability. These events have focused attention on the role of deposit insurers and their role in the banking system. Recent literature has found evidence that during the financial crisis, deposit insurance maintained banking stability and successfully prevented bank runs. On the other hand, research indicated that deposit insurance increased banking instability during non-crises periods. Literature has also highlighted the relationship between banking stability, features of deposit insurance systems such as coverage limits along with economic and institutional factors. Accordingly, this study examines deposit insurance system’s coverage limits and the impact on banking stability, in the context of a jurisdiction’s economic and institutional environment. We run linear regression models examining 63 jurisdictions in Asia and Europe with explicit deposit insurance system, across the time period of 2004-2014, covering the pre and post-financial crisis. We also examine subsets to investigate the effects of region by comparing Asia and Europe as well as a subset using date of establishment of the deposit insurance system to understand if maturity matters. The results indicate that deposit insurance systems, and specifically deposit insurance coverage levels, have both positive and negative effects on banking stability. We find that there are significant associations with certain economic and institutional factors; however, there are differences between the models we ran that we ascribe due to regional factors and also the date of establishment of a deposit insurance system. Therefore, an important takeaway for policymakers is the interplay of the jurisdiction’s cultural factors, economic conditions, types of banking model and the maturity of the deposit insurance system. Another interesting finding was that amongst the five banking measures of stability adopted in the regression models, no single measure appears to be superior in predicting banking stability. In terms of future research, the model we used did not incorporate the perception of financial consumers, in relation to deposit insurance or coverage levels. The element of human behavior has an important role in bank runs and a better understanding of these relationships will assist policymakers in designing more effective deposit insurance systems.